Coping with the milk scandal: A staged approach to crisis communication strategies during China's largest food safety crisis. Issue 4 (19th September 2018) - Zeng, Li; Zhou, Lijie; Pan, Po-Lin; Fowler, Gil
Abstract : Purpose: The purpose of this paper is to examine crisis communication strategies used by four leading Chinese milk companies at various crisis stages to cope with the largest food safety crisis in China. Approaching the interplay between the situational crisis communication theory (Coombs, 2007 ) and the image restoration theory (Benoit, 1995 ), the study attempted to understand the importance of crisis management at various crisis stages by comparing crisis communication strategies used by surviving and thriving companies with those by the company that failed. Design/methodology/approach: Dividing a crisis management process into three stages, a content analysis was conducted to analyze five major crisis communication strategies – evasion of responsibility, rebuilding, bolstering, endorsement of outside experts and government relations – used by Chinese milk companies at various crisis stages. Findings: The study demonstrated that Sanlu, which went bankrupt as a result of the scandal, predominately took the Chinese crisis management approach. The other three companies that survived the scandal employed western crisis communication strategies, although with distinct Chinese characteristics. Specifically, all four companies employed similar strategies during the pre-crisis stage – keeping silent/covering-up. During the crisis stage, strategies varied dramatically as companies became involved – looking for government protection and apologizing, while survivors tended to adopt a widely used western strategy – bolstering at the post-crisis stage. Practical implications: The examination of crisis communication strategies at various crisis stages may shed some light on how effectively Chinese companies and possibly international companies in China can manage future crises that share similar profiles as this milk scandal and further call for attention to scrutinize the social responsibility of corporate citizens in China. Originality/value: This study would fill the vacancy in research by investigating crisis communication strategies used in the largest food safety crisis in China. The findings provide insight for understanding the current status of crisis communication strategies and management within a Chinese matrix of political, social and cultural factors.